The public perception of orthodontic treatment performed by general dentists and specialist orthodontists - Wishney Morgan; Dalci Oyku; Petocz Peter; Darendeliler M. Ali (Sciendo, 2018)
In Australia, orthodontic treatment may be performed by either a general dental practitioner (GDP) or a specialist orthodontist. However, the titles 'specialist' and 'orthodontist' are restricted to dentists who have undertaken an additional three years of full-time training in an accredited institution. Considering the increase in popularity of GDP orthodontic courses, an assessment was worthwhile of the public's understanding of the difference between a specialist orthodontist and a GDP who provides orthodontic treatment.